Functional characterization of biodegradable nanoparticles as antigen delivery system. Issue 1 (December 2015) - Petrizzo, A.; Conte, C.; Tagliamonte, M.; Napolitano, M.; Bifulco, K.; Carriero, V.; De Stradis, A.; Tornesello, M.; Buonaguro, F.; Quaglia, F.; Buonaguro, L.
Background Peptide based vaccines may suffer from limited stability and inefficient delivery to professional antigen-presenting cells (APCs), such as dendritic cells (DCs). In order to overcome such limitations, several types of biodegradable nanoparticles (NPs) have been developed as carrier system for antigens. The present study describes for the first time the extensive biological characterization of cationic NPs made of poly (D, L-lactide-co-glycolide) (PLGA) and polyethylenimine (PLGA/PEI) as delivery system for protein/peptide antigens, with potential in therapeutic cancer vaccine development. Results Flow cytometry as well as confocal laser scanning microscopy (CLSM) showed that PLGA/PEI NPs are more readily taken up than PLGA NPs by both human CD14+ monocytes and mouse Hepa 1–6 hepatoma cell line. No signs of toxicity were observed in either cellular setting. Sequential image acquisition by TEM showed an intracellular apical localization for PLGA NPs and a perinuclear localization for PLGA/PEI NPs. Both NPs showed a clathrin-dependent as well as a caveolin-dependent internalization pathway and, once in the cells, they formed multivesicular endosomes (MVE). Finally, anex vivo priming experiment showed that PLGA/PEI NPs are comparable to PLGA NPs in delivering a non-self antigen (i.e., ovalbumin - OVA) to immature dendritic cells (imDCs), which matured and induced autologous naïve CD4+ T cells to differentiate to memory (i.e., central memory and effector memory) cells. Such a differentiation was associated with a Th1 phenotype suggesting a downstream activation and amplification of a CD8+ T cell cytotoxic response. The same OVA antigen in a soluble form was unable to induce maturation of DCs, indicating that both NP formulations provided an intrinsic adjuvanting effect combined to efficient antigen delivery. Conclusions Our study represents the first report on side-by-side comparison of PLGA and PLGA/PEI NPs as strategy for protein antigen delivery. PLGA/PEI NPs are superior for cellular uptake and antigen delivery as compared to PLGA NPs. Such an evidence suggests their great potential value for vaccine development, including therapeutic cancer vaccines.